The role of compartmentalised cyclic nucleotides in pulmonary endothelial barrier function - Schmidt, L (2015)
The barrier function of the endothelium has been found to decrease in response to cyclic adenosine monophosphate (cAMP) elevations in the cellular cytosol, while it seems to be rescued by increasing cAMP concentrations at the membrane. This suggests that cAMP compartmentalisation may be a regulatory mechanism of barrier function. Barrier dysfunction has been implicated in disease, including chronic obstructive pulmonary disease and oedema. It remains unknown whether cAMP compartmentalisation plays a role in barrier dysfunction. Therefore, it is of interest to investigate whether cAMP is compartmentalised in human pulmonary microvascular endothelial cells (hPMEC) and how this affects barrier maintenance. Here we describe the optimisation of methods to investigate the potential cAMP compartmentalisation in hPMEC. Fluorescence Resonance Energy Transfer (FRET) microscopy allows for high resolution live monitoring of spatiotemporal changes of cyclic nucleotides. FRET membrane targeted and cytosolic sensors, respectively, were developed to compare cAMP regulation in different subcellular locations in space and time. FRET imaging studies in hPMEC have not been undertaken before, therefore cell culture conditions were optimized for this specific purpose. In addition, a chamber that combines FRET imaging with transendothelial resistance (TER) measurements was designed and constructed to determine cAMP compartmentalisation in hPMEC and its contribution to cellular barrier function. Fluorescence imaging confirmed localization of FRET reporters at the membrane and in the cytosol, respectively. Addition of 28 mM HEPES and omission of serum were judged to be appropriate in conducting future FRET experiments in hPMEC. Initial FRET-TER chamber experiments were conducted, confirming that both FRET and TER could be measured with this approach. Preliminary data, employing different stimuli and FRET reporters, are in line with the notion of cAMP is compartmentalised in hPMEC. By further optimisation and development of the methods described here, insight will be gained into the localisation and regulation of cAMP at the subcellular level and its effect on endothelial barrier function. This will help clarify whether local manipulation of cAMP signals may offer alternative approaches to the treatment of barrier function-related pathologies.